Pleistocene Archaeology of the Republic of Djibouti - (:unkn) unknown (My University, 2023)
The Republic of Djibouti (Formerly known as French Somaliland and the French Territory of Afars and Issas) lies at the nexus of important geological, ecological, and contemporary cultural settings in the Horn of Africa. It covers an area of c. 23,200 km and its capital (Djibouti City) contains the main deep-water port in East Africa. Due to its position in the tectonically and depositionally active Afar Depression, and despite its small size, the Republic of Djibouti preserves evidence from all the major technocomplexes of the Pleistocene and abundant vertebrate fossils, including a hominin maxilla. Assemblages attributed to the Oldowan, from either surface collections or more rarely excavation, are present especially in the Gobaad basin. These are often associated with large mammal skeletons, likely reflecting hominin butchery of carcasses along paleolake shores or other aquatic environments. Assemblages attributed to the Acheulean, Middle Stone Age, and Later Stone Age are also well represented in several regions, but mainly from surface collections or limited test trenches.
Keywords: African Research